Contextualised high-intensity running profiles of elite football players with reference to general and specialised tactical roles - Ju, W.; Doran, D.; Hawkins, R.; Evans, M.; Laws, A.; Bradley, P. S. (Biology of Sport, 2023)
The present study aimed to contextualise physical metrics with tactical actions according to general and specialised tactical roles. A total of 244 English Premier League players were analysed by coding player`s physical-tactical actions via the fusion of tracking data and video. Data were analysed across 5 general (Central Defensive Players = CDP, Wide Defensive Players = WDP, Central Midfield Players = CMP, Wide Offensive Players = WOP, Central Offensive Players = COP) and 11 specialised positions (Centre Backs = CB, Full-Backs = FB, Wing-Backs = WB, Box-to-Box Midfielders = B2BM, Central Defensive Midfielders = CDM, Central Attacking Midfielders = CAM, Wide Midfielders = WM, Wide Forwards = WF, Centre Forwards = CF). COP covered more distance at high-intensity (> 19.8 km· h-1) when performing actions such as `Break into Box`, Run in Behind/Penetrate`, and `Close Down/Press` than other positions (ES: 0.6-5.2, P < 0.01). WOP covered more high-intensity `Run with Ball` distance (ES: 0.7-1.7, P < 0.01) whereas WDP performed more `Over/Underlap` distance than other positions (ES: 0.9-1.4, P < 0.01). CDP and WDP covered more high-intensity `Covering` distances than other positions (ES: 0.4-2.4, P < 0.01). Nonetheless, data demonstrated that implementing specialised positional analysis relative to a generalised approach is more sensitive in measuring physical-tactical performances of players with the latter over or underestimating the match demands of the players compared to the former. A contextualised analysis may assist coaches and practitioners when designing position or even player-specific training drills since the data provides unique physical-tactical trends across specialised roles.